Thymus: the next (re)generation. Issue 1 (May 2016) - Chaudhry, Mohammed S.; Velardi, Enrico; Dudakov, Jarrod A.; van den Brink, Marcel R. M.
Summary: As the primary site of T‐cell development, the thymus plays a key role in the generation of a strong yet self‐tolerant adaptive immune response, essential in the face of the potential threat from pathogens or neoplasia. As the importance of the role of the thymus has grown, so too has the understanding that it is extremely sensitive to both acute and chronic injury. The thymus undergoes rapid degeneration following a range of toxic insults, and also involutes as part of the aging process, albeit at a faster rate than many other tissues. The thymus is, however, capable of regenerating, restoring its function to a degree. Potential mechanisms for this endogenous thymic regeneration include keratinocyte growth factor (KGF) signaling, and a more recently described pathway in which innate lymphoid cells produce interleukin‐22 (IL‐22) in response to loss of double positive thymocytes and upregulation of IL‐23 by dendritic cells. Endogenous repair is unable to fully restore the thymus, particularly in the aged population, and this paves the way toward the need for exogenous strategies to help regenerate or even replace thymic function. Therapies currently in clinical trials include KGF, use of the cytokines IL‐7 and IL‐22, and hormonal modulation including growth hormone administration and sex steroid inhibition. Further novel strategies are emerging in the preclinical setting, including the use of precursor T cells and thymus bioengineering. The use of such strategies offers hope that for many patients, the next regeneration of their thymus is a step closer.